2016
DOI: 10.1108/cg-05-2015-0065
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the quality of social and environmental disclosures by Nigerian oil companies

Abstract: Purpose This study seeks to examine the quantity and quality of social and environmental disclosures (SEDs) of Nigerian oil companies. The study aims to analyse SED activities as reported by the oil companies in their annual reports. Design/methodology/approach The study analyses annual reports through content analysis. SED quantity is measured by alternative two units: number of sentences and number of pages. A two-point scale system to assess SED quality is used as follows: 1 = if SED is quantitative and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 89 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…Content analysis of sustainability reporting can be particularly useful at this early stage of research, when the main purpose is starting an initial recognition of the problem at hand, at a national level. Similar country studies can be found in the literature, such as the content analysis of social and environmental reports of Nigerian oil companies (Odera et al, 2016), or the analysis of the sustainability reports of ten large-scale mining companies in Ghana (Arthur et al, 2017). 2016 was selected as reference year taking into account that the SDGs were globally adopted in September 2015, so the 2016 reports would give account of the first year after global adoption.…”
Section: Methodsmentioning
confidence: 99%
“…Content analysis of sustainability reporting can be particularly useful at this early stage of research, when the main purpose is starting an initial recognition of the problem at hand, at a national level. Similar country studies can be found in the literature, such as the content analysis of social and environmental reports of Nigerian oil companies (Odera et al, 2016), or the analysis of the sustainability reports of ten large-scale mining companies in Ghana (Arthur et al, 2017). 2016 was selected as reference year taking into account that the SDGs were globally adopted in September 2015, so the 2016 reports would give account of the first year after global adoption.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the relevance of SED was incorporated through three variables related to SR's integration into business strategy, the presence of an SR committee and, finally the achievement of any SR award. The unresolved theoretical debate around the concept of quality itself determines the difficulty of defining how to measure it (Odera et al, 2016). In an attempt to resolve this, we selected the most repeated variables used by previous papers with empirical support of their relationship with the quality approach.…”
Section: Sampj 123mentioning
confidence: 99%
“…In this guise, firms may hide behind weak institutional structures and relegate their CSR to the background.Hence, we argue that MNCs' PMA succeeds within ODCs where weak institutional structures abound. Such weak institutional context therefore, holds the implication that legal, regulatory and judicial systems within ODCs are not strong enough to hold MNCs accountable for their actions and inactions Odera et al (2016). investigate the quality of social and environmental disclosures by oil and gas MNCs (MNCs) and find that low quality social and environmental disclosures drive their business profit maximisation agenda.…”
mentioning
confidence: 99%